KEHIDUPAN SYLVIA PLATHDALAM PUISI-PUISINYA - Eman, Jeff Bruscel (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This Skripsi entitled ?The Reflection of Sylvia Plath?s Poems in Her Life? rejects the common people?s opinion that poems are only about sentimentalism and exaggeration of ideas. There are eight poems analyzed in this research. To analyze these poems, the writer used the extrinsic and intrinsic approach. The extrinsic approach includes the condition of social life in the surrounding of Sylvia Plath, and the intrinsic approach includes the element that build the proper poem. The result shows that almost all Sylvia Plath?s poems are connected with her life and people around her, and how worse her life when she live. Keywords:       Reflection, Sylvia Plath, Poems, The Extrinsic and Intrinsic Approach